Depiction of Goddess Yamuna, Dvarapala and Lord Kartikeya - Temples of India Project Team (Jio Institute, 2024)
On the proper left side of the doorframe, the river Goddess Yamuna is depicted standing on a pedestal, with her vahana (mount), a kachhapa (tortoise), shown on the same pedestal. Next to her, a Shaiva dvarapala (door guardian) is depicted with his two attendants, one male and one female. Beneath this, a niche is carved, featuring a figure of Kartikeya with three heads, holding his weapon, the spear, in front.